Position Tracking Performance for ElectroHydraulic Actuator System with the Presence of Actuator Internal Leakage - Shern, C. M.; Ghazali, R.; Soon, C. C.; Sam, Y. M.; Rahmat, M. F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
Electro-hydraulic actuator (EHA) system is known as one of the highly nonlinear systems due to its parameters uncertainties. Many types of robust controller had been studied and proposed to control the nonlinear EHA system. Different parameters uncertainties test is needed in the procedure to evaluate the controller robustness. In this paper, the effect of the actuator internal leakage to the output actuator displacement is studied. The actuator output displacement is analyzed using Root Mean Square Error (RMSE) by means of giving sinusoidal input reference. The results show that as the actuator internal leakage increases, the RMSE will increase and the actuator will start to vibrate or show damping characteristics.